Ignoring environmental change? On fishing quotas and collapsing coastlines in Bykovskiy, Northern Sakha (Yakutiya) - Olga Povoroznyuk (Department of Social and Cultural Anthropology, Faculty of Social Sciences, University of Vienna); Peter Schweitzer (Department of Social and Cultural Anthropology, Faculty of Social Sciences, University of Vienna) (Ambio, 2023)
The abstract is available here: https://uscholar.univie.ac.at/o:2023411 The abstract is available here: https://uscholar.univie.ac.at/o:2023411